Crustacean Hyperglycemic Hormone and Gonad Histology of Female Spiny Lobster (Panulirus homarus) Inducted by Laserpuncture - Jonathan Christian Wibowo; Mohamad Fadjar; Yunita Maimunah (Jurnal Penelitian Pendidikan IPA, 2024)
Spiny lobster is one of the potential commodities in Indonesia. On the other hand, there is still a problem to fulfill the export-ready stock of spiny lobster. Production engineering can be utilized as one way to overcome the existing problems. Laserpuncture is a new method of production engineering by utilizing low wavelength helium-neon light that can provide biological stimulation to living things resulting in accelerated development. Laserpuncture induction in crustaceans such as lobsters can be done on the eye stalk and ventral part. This study was conducted using completely randomized design method with 4 treatments and 5 repetitions of each treatment. The treatments given are differences in the duration of laserpuncture induction on female spiny lobster including A (2 seconds induction), B (4 seconds induction), C (6 seconds induction), and control (without induction). This study aims to analyze wheter laserpuncture affects Crustacean Hyperglycemic Hormone. CHH and gonad in female spiny lobster. Data analysis in this study was carried out qualitatively which included Crustacean Hyperglycemic Hormone A & B hormone, gonad histology, and survival rate. The results showed that treatment A (2 seconds induction of laserpuncture) on female spinny lobster had the most significant effect compared to other treatments.